What is wrong with the beard : Eisenstein’s Ivan the Terrible as an eccentric tragedy - Tsivian, Yuri (Cinémas, 2001)
ABSTRACTThe article looks at some idiosyncrasies of Eisenstein's set design, make-up and lighting for Ivan the Terrible (1945) from three points of view : the first, through the eyes of its Kremlin censors; the second, through the lens of Eisenstein's working notes; the third, through the eyes of the American film director (and part-time film critic) Orson Welles. The author attempts to define what general audiences of the 1940s understood as "cinematic" and "pictorialist" and how Eisenstein's paradoxical film theory and theory of art allowed him to reverse this generally accepted division.